High prevalence of Blastocystis spp. in children from a periurban school - Cazorla-Perfetti, Dalmiro J. (2017)
Mr. Editor We have read with great interest and interest the research work of Quispe-Juli et al (1) carried out in the Ciudad de Dios population, located in the District of Yura, Arequipa, Peru. In this paper, we present the results of a co-parasitological study to determine the prevalence of Blastocystis spp., Etiological agent of blastocystosis or Zierdt-Garavelli disease, and other enteroparasites in 83 school children.